Preliminary Study on the Influence of Blade Shape and Quantity in Water Turbines using the INA219 Sensor - MONAESA SAGALA; ELLIN ERNITA MAHDALYA; YOSIA PANDU SIHOMBING; TRESI PITRIA ULANDARI; EVI SULISTIANI; ELFI YULIZA; RISKA EKAWITA (Institut Teknologi Nasional, Bandung, 2025)
The design of turbine blades plays a crucial role in enhancing the efficiency of converting the kinetic energy of water into electrical energy, particularly on a small scale. This study aims to evaluate the influence of blade shape and number on turbine performance, as well as to compare the accuracy of voltage measurements using an INA219 sensor based on Arduino Uno with a digital multimeter. Four blade shapes were tested: cylindrical, semi-cylindrical, concave oval, and flat plate, each configured with 4 and 8 blades. Tests were conducted under three water flow rate conditions (low, medium, and high) to observe the optimization process of turbine performance. The results showed that the cylindrical blade with 8 blades produced the highest voltage of 1.03 V at high flow rate. The average measurement difference between the sensor and the multimeter was ±0.015 V, indicating good accuracy. These findings confirm that the cylindrical blade is the most efficient, and the INA219 sensor based on Arduino is suitable for use in micro-hydro turbine voltage monitoring systems.